Relações de gênero, trabalho e formação docente : experiências de mulheres da Escola Estadual Valnir Chagas, Aracaju/SE - Santana, Anabela Mauricio de (2014)
This research aimed to analyse under the perspective of gender, the sense, the meaning of work, the valuation of qualification and new skills for the Primary Education teachers of the State School Professor Valnir Chagas in the city of Aracaju/SE, highlighting advances achieved in the identity construction, the expansion of rights and citizenship. For the object of study configuration, it was necessary some incursions among the Sociology and Education areas. The adopted historical-dialectical referential assumes that all human activities are mediated by culture, in other words, in the case of human beings there are not natural phenomena. Thus, gender relations are social constructions that have got material basis and represent the production process of the seats of power of men and women in society.The preferential option for the qualitative research, of study case type, refers to the fact that it may either analyse a unit or multiple studies, since a case is a specific unit, a delimitated system whose parts are integrated. The methodology fell in the qualitative approach for permitting the collection and analysis of data in depth regarding the explicit and implicit aspects of the studied phenomenon, besides providing the explanation of subjectivities, in other words, not only the social, economic, political, ideological and cultural aspects become evident, but the ways of thinking, acting and feeling of the studied subjects as well, dating back to facts that outline the reality, seizing the constitutive and determinants causes of phenomena.The methodological approach proved relevant to the knowledge of concrete work situations of teachers so that, through social relationships observed, it may be appointed elements able to inform analyses that contributed to a better understanding of transformations in the social gender relations. Different sources of information were consulted: documents, official statistics, prioritizing oral sources through semi-structured interviews conducted with seven teachers of that school. The dialectic of differences emerges in the senses and meanings attributed to work and qualification. The teachers do not show familiarity with the gender approach, they tend to express naturalised representations about the differences construction. The social and sexual historical division of labour complicates the process of identity construction, and therefore the expansion of rights and citizenship. Even before the faced difficulties, they contradictorily regard that the gender attributes do not affect their professional projects construction and vice versa, defining possibilities of qualification and mobility in the labour market.